Modelling and Experimental Study of Dissimilar Arc Stud Welding of AISI 304L to AISI 316L Stainless Steel - Marwan T. Mezher; Osamah Sabah Barrak; Nasri S. M. Namer (International Journal of Integrated Engineering, 2022)
This paper has aimed to try and establish a successful weld joint between AISI 304L stainless steel as a stud and AISI 316L stainless steel as a plate by using an arc stud welding process. The effect of different current and time welding on the torque results was experimentally studied, by using three-level of each process parameter. The post-weld heat treatment (PWHT) was carried out on the optimum sample of torque, to study the effect of PWHT on mechanical properties (torque and hardness) and microstructure of the welding zone. In the present work, A 3-D finite element model was developed by using ANSYS software version 18 to analyze the influence of time and current welding on the temperature distribution and residual stresses of the resultant welded joints. A transient thermal model was built to predict the temperature distribution whereas the residual stresses were determined by using a static structural model. The PWHT has been used to reduce the amount of residual stresses and enhance the mechanical properties of the welded joint. The micro-hardness based on the Vickers test and the microstructure of welded specimens with and without PWHT have been investigated. The simulation results reveal that the generated temperature and the residual stress is strongly affected by the time and current welding. The mechanical test results indicated that the PWHT prompted an improvement in the hardness values.